Use of Extracorporeal Membrane Oxygenation in Patients with Refractory Cardiac Arrest due to Severe Persistent Hypothermia: About 2 Case Reports and a Review of the Literature. (5th November 2021) - Attou, Rachid; Redant, Sébastien; Preseau, Thierry; Mottart, Kevin; Chebli, Louis; Honore, Patrick M.; De Bels, David; Gallerani, Andrea
Abstract : We report the cases of two patients experiencing persistent severe hypothermia. They were 45 and 30 years old and had a witnessed cardiac arrest managed with mechanized cardiopulmonary resuscitation (CPR) for 4 and 2.5 hours, respectively. Extracorporeal membrane oxygenation was used in both patients who fully recovered without any neurological sequelae. These two cases illustrate the important role of extracorporeal CPR (eCPR) in persistent severe hypothermia leading to cardiac arrest.